The Application of a Game-Based Learning Model Based on Ethnomathematics to Improve Mathematical Creative Thinking Ability - hilliyani, hilliyani; Muhammad Amin Fauzi, KMS; Mulyono, Mulyono (Perspektif Pendidikan dan Keguruan, 2025)
The purpose of this research is to analyze mathematical creative thinking abilities that are obtained from learning Game-Based Learning and conventional learning. This research used quantitative research with quasi experiment design and pretest posttest control group design. The population in this research was all students at SMP N 1 Takengon. The sample of this research were the students class VIII B for experiment class and students class VIII C for control class. The instrument used was test about mathematical creative thinking abilities students pretest and posttest. The technique of data analysis used in this research was paired t test. The result of this research was paired t test showed sig. so H rejected and H accepted. In the other word there was improvement mathematical creative thinking abilities used the implementation of learning model Games-Based Learning based on Etnomatematika